The prevalence of suicide attempt and suicidal ideation and its relationship with aggression and bullying in Chilean adolescents - Veloso-Besio, Constanza; Cuadra-Peralta, Alejandro; Gallardo-Peralta, Lorena; Cuadra-Fernandez, Pascal; Quiroz, Pedro Trujillo; Troncoso, Nicole Vega (Frontiers in Psychology, 2023)
Background Suicide constitutes one of the main mental health problems worldwide, requiring detection, and prevention efforts, especially in the adolescent population. Objective The purpose of this study was to estimate the prevalence of suicide attempts and suicidal ideation and their relationship with aggressiveness and bullying in Chilean adolescents. Materials and methods The sample was composed of 728 adolescents schooled from Arica city: 56.6% were males and 43.4% were females. The students attended from de 1st to the 4th year of secondary. The average age of the sample was 15,6 years. The following instruments were used: Okasha’s Suicidality Scale, Buss and Perry’s Aggressiveness Survey, and the Social Acceptance (School Bullying) sub-test of the Kidscreen-52 Survey. A cross-sectional, descriptive, and correlational design was applied. The sampling was non-probabilistic for convenience. Results 18.4% of the students reported that they had attempted suicide and 65.6% reported that they had suicidal ideation. The prevalence of suicide attempts was higher than in male adolescents (29,1% vs. 10,2%), and the same prevalence was for suicidal ideation (76,6% vs. 57,3%). Suicide attempts and suicidal ideation were positively and significantly correlated with aggressiveness (r = 0.32, r = 0.48) and bullying (r = 0.37, r = 0.50). Conclusion The prevalence of suicide attempts and suicidal ideation is both higher in girls than boys. In this sense, girls constitute a risk group. In addition, this study provides evidence that supports the relationship between suicide attempts and suicidal ideation. The results highlight the role that educational institutions should have in terms of prevention and effective approaches.